On the territory of mystery in film and painting - Pascual Galbis, Pau (2020)
Study of the arcane expression mystery, and present in the cinema of David Lynch, and Alfred Hitchcock, to more than the painting of René Magritte and Giorgio de Chirico. Therefore, this research article investigates this ability in an interdisciplinary and poetic way, relating the works of artists closely related to the visual arts and the moving image. Parallel tours of Surrealism, the unconscious and the uncanny. Strange objects, luxurious mansions, deranged characters, unsolved murders and most of all, many streets with long shadows. Sublime plots and landscapes that all coincide towards the ritual of the incognito. Prelude to future adversities.